Nutritional Status of Children: The Correlation of Socioeconomic Status and Parental Involvement - Sitorus, Ahmad Syukri; Yufiarti,; Mahdiyah, (International Journal of Psychosocial Rehabilitation, 2020)
Nutrition plays a major role in the health and development of children. The nutritional status of children is also related to the children's development and their achievements in the future. This study aims to find out the correlation between socioeconomic status and parental involvement toward the nutritional status of children. The sample consisted of 109 early children aged 5-6 years. The data analysis technique used was multiple regression with two predictors and partial correlation. The results proved that there was a significant correlation between socioeconomic status and parental involvement toward the nutritional status of children. Then, there was a significant correlation between socioeconomic status and nutritional status of children by controlling the variables of parental involvement, and there was a significant correlation between parental involvement and nutritional status of children by controlling socioeconomic status variables.